Development as freedom? Insights from a farmer-led sustainable agriculture non-governmental organisation in the Philippines. (October 2022) - Jack, Gavin; Plahe, Jagjit; Wright, Sarah
This study addresses freedom, work and organisation by problematising Amartya Sen's pluralistic notion of (development as) freedom through a fieldwork study of a Filipino non-governmental organisation that promotes sustainable agriculture. In this context, peasant farmers face increasing threat from intersecting agrarian and climate crises, exacerbated by mainstream economic paradigms for agricultural development. For Sen, development encompasses the process of expanding the 'substantive freedoms' of people (freedom to), and removing sources of 'unfreedom' (freedom from). However, it is not clear in Sen's work how such freedoms are relationally constituted and thus the manner of the 'labour of agential becoming' at the core of Sen's thought. We therefore ask: how do agroecological work and organisational practices of grassroots development promote freedom for small-scale farmers under climate threat in the Global South? Our analysis identifies a novel form of freedom – labelled 'freedom with' – defined as a set of relational, multi-actor capabilities and organising practices that constitute alternative, future-oriented ways of doing and being. 'Freedom with' enables us to better understand how and why the labour of agential becoming works, offering a theoretical extension of Sen's notion of freedom with implications for debates in our field on sustainability and beyond-capitalist organising.